Determinan Peringkat Sukuk di Indonesia Periode 2015-2019 - Fisabilillah Hadisyah Siregar; Egi Arvian Firmansyah (Jurnal Iqtisaduna, 2022)
This research aims to find out the whether the financial and non-financial factors affect corporate sukuk rating (dependent variable) in Indonesia in 2015-2019. In this research, we employ profitability, liquidity, leverage, secure and firm size as the independent variables. This research uses the secondary data from financial statements available at Indonesia Stock Exchange and the company’s web. The object of this research is all companies receiving rating sukuk from PT PEFINDO. This research uses a quantitative approach with ordinal logistic regression while the sample is obtained through a purposive sampling method. The results show that profitability, liquidity, secure and firm size have a significant effect on sukuk rating, meanwhile leverage does not have a significant effect on sukuk rating.